Exploring the impact of nature connectedness on well-being and mental distress among urban youth: Evidence from 25 most populated cities in India - Raina Chhajer; Sudeep R. Bapat (PLoS ONE, 2025)
In contemporary urban settings, enhancing the well-being of youth is a challenge. The proliferation of screen time, particularly post-pandemic, has contributed to an alarming disconnection with nature. This study investigates the impact of nature connectedness on the well-being of urban youth residing in the 25 most populated cities in India. 2283 urban youth responded to an online survey questionnaire that aimed to assess participants’ exposure to and interaction with nature. Respondents self-reported their proximity to green and blue spaces near their residences, the frequency of recreational visits to these areas, time spent in indoor environments, nature connectedness, and well-being. Multivariate regression analysis results show that urban youth with access to both green and blue spaces within 1-kilometre or between 1-3 kilometres radius, along with frequent recreational visits to these spaces, reported a significant positive impact on well-being. Additionally, spending less than 8 hours in indoor environments and a high nature connectedness score had a significant positive impact on well-being. Moreover, a logistic regression analysis shows that urban youth with well-being score less than 13, considered mentally distressed, who have access to both green and blue spaces within 1 kilometres or access to green spaces between 1-3 kilometres, along with frequent recreational visits to these spaces, and a high nature connectedness score, increases their log-odds of well-being significantly. This study conducted in the 25 most populated cities, represents a comprehensive exploration of the impact of nature connectedness on well-being in India. The study does, however, have limitations, including uneven sample distribution among cities, the absence of temporal analysis, and a restricted age range of 18-25 years. These limitations will be addressed in future research. The implications of the study extend to policy recommendations, advocating for the development of more parks in close proximity to residential areas. Such initiatives aim to encourage urban youth to actively engage with and experience nature, fostering improved well-being and reduced distress levels.